Exploration of Students' Experiences with Mobile-Based Mathematics Learning Media: A Study of MTs Students in Pasuruan - Ariansyah, Fitroh; Muhammad Yousaf Farooq, Syed; Munif, Ahmad (Delta-Phi: Jurnal Pendidikan Matematika, 2025)
-In today's digital era, educational innovation is crucial for improving student learning, particularly in mathematics, which is often perceived as challenging. This study explores students' experiences and perceptions of the use of mobile-based mathematics learning media at the Madrasah Tsanawiyah (MTs) level in Pasuruan Regency. Using a qualitative approach, nine ninth-grade students were selected as primary participants. Data were collected through in-depth interviews, participant observation, and focus group discussions (FGDs), allowing researchers to understand the dynamics of students' interest, engagement, and challenges during mobile learning. Data analysis was conducted thematically to identify patterns in student experiences, perceived ease of use, and the impact of mobile media on understanding mathematical concepts such as algebra and geometry. The results showed that the majority of students experienced increased interest and engagement in learning thanks to the interactive features and flexible access offered by mobile media. Students also reported improved understanding of previously difficult material. However, several challenges remained, such as the need for technical assistance and adaptation to new methods. This study emphasizes the importance of a qualitative approach in understanding student learning experiences and provides recommendations for developing digital learning media that are responsive to student needs. These findings are expected to serve as a reference for educators and educational technology developers in designing more effective and meaningful learning innovations.